Effect of activator, curing and humidity on drying shrinkage of alkali-activated fly ash. Issue 2 (15th February 2019) - Hojati, Maryam; Rajabipour, Farshad; Radlińska, Aleksandra
Abstract : Alkali-activated fly ash (AAFA) concrete is receiving considerable attention due to its environmental benefits; however, its long-term performance still requires validation and laboratory verification. This research studied the drying shrinkage of AAFA pastes as a function of activator composition (water content and n -modulus), relative humidity (RH) and heat-curing duration. Four AAFAs activated by different sodium silicate solutions and a control ordinary Portland cement (OPC) were examined. The activating solution affected the pore structure, pore solution and shrinkage characteristics of AAFAs. Use of an activator with a higher n -modulus resulted in a finer pore structure, superior mechanical properties and a larger magnitude of shrinkage. The results indicate that heat-cured AAFA paste dried faster, and its shrinkage reached equilibrium earlier compared to that of OPC. Similar to OPC, a bilinear relationship between RH and shrinkage of AAFA was observed. The results indicate that a longer steam-curing duration can stabilize the matrix of AAFAs and reduce their shrinkage.